2014
DOI: 10.1177/1933719113492211
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol 17β and Its Metabolites Stimulate Cell Proliferation and Antagonize Ascorbic Acid-Suppressed Cell Proliferation in Human Ovarian Cancer Cells

Abstract: Estradiol 17β (E2β) and ascorbic acid (AA) have been implicated in cancer progression. However, little is known about the actions of biologically active metabolites of E2β, 2-hydroxyestradiol (2OHE2), 4-hydroxyestradiol (4OHE2), 2-methoxyestradiol (2ME2), and 4-methoxyestradiol (4ME2) synthesized sequentially by cytochrome P450, family 1, subfamily A (CYP1A1) and B (CYP1B1), polypeptide 1, and catechol-O-methyltransferase (COMT) on ovarian cancer. Herein, we examined the expression of CYP1A1, CYP1B1, COMT, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…It is well recognized that MOE induces mitotic arrest and apoptosis in carcinoma cells [31]. However, in ovarian carcinoma cells lacking PRODH/POX [32], on the contrary, MOE stimulated cell proliferation [33]. The discrepancy may suggest that the underlying mechanism of this phenomenon could involve other factors than the proline availability and PRODH/POX activity.…”
Section: Discussionmentioning
confidence: 74%
“…It is well recognized that MOE induces mitotic arrest and apoptosis in carcinoma cells [31]. However, in ovarian carcinoma cells lacking PRODH/POX [32], on the contrary, MOE stimulated cell proliferation [33]. The discrepancy may suggest that the underlying mechanism of this phenomenon could involve other factors than the proline availability and PRODH/POX activity.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, ascorbic acid (AA), a naturally compound with antioxidant properties and one form of Vitamin C, has been implicated in preventing and treating cancers (22). The exact roles of estrogen and its active metabolites in the development of ovarian cancer is still controversial (1,23,24), the role of AA in cancer prevention and treatment is still not conclusive (23). In one of studies, Li et al examined the roles of estrogen and its active metabolites in the ovarian cancer progression (23).…”
Section: Sex Hormonesmentioning
confidence: 99%
“…In one of studies, Li et al examined the roles of estrogen and its active metabolites in the ovarian cancer progression (23). Li et al firstly found that the expression of cytochrome P450, family 1, subfamily A (CYP1A1) and B (CYP1B1), polypeptide 1, and catechol-O-methyltransferase (COMT), ERα, and ERβ in most cell lines tested including human ovarian surface epithelial (IOSE-385) and cancer cell lines (OVCAR-3, SKOV-3, and OVCA-432) (23). Active metabolites of estradiol 17 β (E2β, a steroid and estrogen sex hormone) including 2-hydroxyestradiol (2OHE2) (23).…”
Section: Sex Hormonesmentioning
confidence: 99%
See 2 more Smart Citations